2009
DOI: 10.1002/etc.31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary cadmium exposure on reproduction of saltwater cladoceran Moina monogolica Daday: Implications in water quality criteria

Abstract: The chronic toxicity of dietary cadmium to the saltwater cladoceran Moina monogolica Daday and its relative toxicity compared with aquatic exposure were investigated in the present study. The microalgae Chlorella pyrenoidosa, exposed to cadmium in growth inhibition tests, had a 96-h median effective concentration (EC50) of 81.2 microg Cd/L (95% confidence intervals [CIs] = 71.9-95.1). C. pyrenoidosa exposed for 96 h to sublethal dissolved cadmium concentrations in the range 4.10 +/- 0.30 to 70.29 +/- 0.31 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…Several studies have demonstrated the importance of dietborne in metal exposure and toxicity to zooplankton. Production of neonates by Daphnia magna was significantly reduced when its diet (Pseudokirchneriella subcapitata) was contaminated with Cd (Geffard et al 2008); toxic effects were observed on the survival and reproductive aspects of Moina monogolica fed on Cd contaminated Chlorella pyrenoidosa (Wang et al 2010). Similar effects on fecundity and survival were reported for other daphnid species like Ceriodaphnia dubia (Rodgher and Espíndola 2008).…”
Section: Introductionsupporting
confidence: 73%
“…Several studies have demonstrated the importance of dietborne in metal exposure and toxicity to zooplankton. Production of neonates by Daphnia magna was significantly reduced when its diet (Pseudokirchneriella subcapitata) was contaminated with Cd (Geffard et al 2008); toxic effects were observed on the survival and reproductive aspects of Moina monogolica fed on Cd contaminated Chlorella pyrenoidosa (Wang et al 2010). Similar effects on fecundity and survival were reported for other daphnid species like Ceriodaphnia dubia (Rodgher and Espíndola 2008).…”
Section: Introductionsupporting
confidence: 73%
“…However, zinc concentrations in the hepatopancreas from all deployment sites were in the same range as those reported for the reference site. One possible reason is that the shrimp have developed mechanisms to regulate accumulation of zinc as essential metal or the organisms taken from the aquaculture farm had a high background concentration of zinc (Wang et al 2010). Surprisingly, zinc concentrations were much lower than copper concentrations in the hepatopancreas of L. vannamei, which is different from the relationships between zinc and copper concentrations in tissues of other organisms such as bivalves.…”
Section: Discussionmentioning
confidence: 93%
“…The suspended solids in the water are a mixed collection of different materials, resuspended sediment, colloids, fecal material, organic decomposition materials, etc., which can easily adsorb metals and could constitute a source of contamination and toxicity for aquatic organisms (Wang et al 2010). As one component of aquatic ecosystems that are important for metal transport, suspended solids can produce more direct impacts on aquatic ecosystems and can reflect the real-time status of water pollution as a better indicator than sediment (Zhu et al 2005).…”
Section: Introductionmentioning
confidence: 99%